2016
DOI: 10.18632/oncotarget.9572
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-320a inhibits breast cancer metastasis by targeting metadherin

Abstract: Dysregulated microRNAs play important pathological roles in carcinogenesis that are yet to be fully elucidated. This study was performed to investigate the biological functions of microRNA-320a (miR-320a) in breast cancer and the underlying mechanisms. Function analyses for cell proliferation, cell cycle, and cell invasion/migration, were conducted after miR-320a silencing and overexpression. The specific target genes of miR-320a were predicted by TargetScan algorithm and then determined by dual luciferase rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 35 publications
3
42
0
Order By: Relevance
“…The miRNA has been demonstrated to inhibit breast cancer metastasis and invasion [28, 29] while also sensitizing breast cancer cells to chemotherapy [30, 31]. Additionally, miR-320a has been observed to be an independent prognostic factor where decreased miR-320a expression is correlated with lower survival in invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA has been demonstrated to inhibit breast cancer metastasis and invasion [28, 29] while also sensitizing breast cancer cells to chemotherapy [30, 31]. Additionally, miR-320a has been observed to be an independent prognostic factor where decreased miR-320a expression is correlated with lower survival in invasive breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicated miR-320a inhibited gastric cancer cell proliferation by downregulating FoxM1 10 and suppressed cancer metastasis by directly targeting metadherin. 11 It can also inhibit cell proliferation of leukemia 12 and colon cancer. 13 Downregulation of its expression is associated with a poor prognosis of clinical patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic expression of miR-205 in MDA-MB-231 cells inhibits cell proliferation, invasion, anchorage independent growth and experimental metastases to the lungs (153). miR-320a acts by suppressing metadherin (MTDH) expression and is down-regulated in BC tissues and cell lines (154). MTDH expression is related to breast cancer progression (155).…”
Section: Further Breast Cancer Metastasis-suppressive Mirsmentioning
confidence: 99%
“…MTDH expression is related to breast cancer progression (155). miR-320a suppresses lung metastases of MDA-MB-231 cells (154).…”
Section: Further Breast Cancer Metastasis-suppressive Mirsmentioning
confidence: 99%